Effect of Ethanol Extract of Cinnamon Bark (Cinnamomum burmanii) on the Lipid Profile and Malondialdehyde of Dyslipidemic Rats - Dewi Ratih Handayani; Sylvia Mustika Sari Sari; Muhammad Danil Hadyan Darojat; Elok Yana Permatasari; Maman Djamaludin (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2023)
Dyslipidemia is a risk factor for atherosclerosis. Dyslipidemia conditions and malondialdehyde (MDAs) increased can cause oxidative stress. Cinnamon contains antioxidant compounds that have a hypolipidemic effect. This study aimed to determine the effect of cinnamon bark ethanol extract on triglycerides, total cholesterol, LDL, HDL, and MDA in dyslipidemic rats. In this study, rats were divided into five groups, a negative control group: which received standard feed, a positive control group: which received a high-fat diet and PTU, the groups that received a high-fat diet, PTU, cinnamon bark ethanol extract (EECB) 125 mg/Kg BW, 250 mg/Kg BW, 500 mg/Kg BW. The results of the analysis showed a decrease in triglyceride levels in all groups given EECB (p <0.05). Total and LDL cholesterol levels decreased in the 125 mg/Kg BW EECB group, and malondialdehyde decreased in the 500 mg/Kg BW EECB group (p <0.05). HDL levels did not increase. The ethanol extract of cinnamon bark was able to improve lipid profiles because it contains cinnamaldehyde and quercetin that can inhibit HMG CoA reductase activity, as well as flavonoids, tannins, and cinnamate which are able to reduce triglyceride and MDA levels. Keywords: cinnamon, dyslipidemia, malondialdehyde, lipid profile.